Gestatten: Keine*r! (Pedagogical Horizons, 2021)
This article offers educational material and accompanies a short graphic novel in the style of a children's book with the title "Gestatten: Keine*r" ("May I introduce myself: Nobody", edited by Takad Zimt, illustrations by Conny Wolf, Sipbachzell: Verlag Am Rande 2021). The aim of the book is to incite civic education, interreligious and intercultural competence and to reflect the abilities of multilingualism. It addresses especially school children and young adults.
Keywords: educational material; civic education; world view pluralism; multilingualism; language acquisition